Structural variation in 1,019 diverse humans based on long-read sequencing - Siegfried Schloissnig; Samarendra Pani; Jana Ebler; Carsten Hain; Vasiliki Tsapalou; Arda Söylev; Patrick Hüther; Hufsah Ashraf; Timofey Prodanov; Mila Asparuhova; Hugo Magalhães; Wolfram Höps; et al. (Nature, 2025)
Abstract Genomic structural variants (SVs) contribute substantially to genetic diversity and human diseases 1–4 , yet remain under-characterized in population-scale cohorts 5 . Here we conducted long-read sequencing 6 in 1,019 humans to construct an intermediate-coverage resource covering 26 populations from the 1000 Genomes Project. Integrating linear and graph genome-based analyses, we uncover over 100,000 sequence-resolved biallelic SVs and we genotype 300,000 multiallelic variable number of tandem repeats 7 , advancing SV characterization over short-read-based population-scale surveys 3,4 . We characterize deletions, duplications, insertions and inversions in distinct populations. Long interspersed nuclear element-1 (L1) and SINE-VNTR-Alu (SVA) retrotransposition activities mediate the transduction 8,9 of unique sequence stretches in 5′ or 3′, depending on source mobile element class and locus. SV breakpoint analyses point to a spectrum of homology-mediated processes contributing to SV formation and recurrent deletion events. Our open-access resource underscores the value of long-read sequencing in advancing SV characterization and enables guiding variant prioritization in patient genomes.